2019
DOI: 10.1016/j.neurobiolaging.2018.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Expression of neurogenic markers in Alzheimer's disease: a systematic review and metatranscriptional analysis

Abstract: Alzheimer's disease (AD) is the most common form of dementia characterized by substantial neuronal loss and progressive brain atrophy. Animal studies have suggested that the process of adult neurogenesis might be altered at the earliest phases of disease onset. The relationship between AD progression and adult neurogenesis in the human brain is, however, not well understood. Here, we present a systematic review of the post-mortem studies that investigated changes in human adult neurogenesis in the AD brain. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 75 publications
(120 reference statements)
0
13
0
Order By: Relevance
“…Attempts have been made to determine the state of AHN in AD patients. However, findings in patients are mixed and inconclusive (reviewed in Gatt et al, 2019). Two recent studies, Moreno-Jimé nez et al (2019) and Tobin et al (2019), confirmed the existence of human AHN and neurogenic changes in AD patients.…”
mentioning
confidence: 99%
“…Attempts have been made to determine the state of AHN in AD patients. However, findings in patients are mixed and inconclusive (reviewed in Gatt et al, 2019). Two recent studies, Moreno-Jimé nez et al (2019) and Tobin et al (2019), confirmed the existence of human AHN and neurogenic changes in AD patients.…”
mentioning
confidence: 99%
“…This could be due to both markers are not fully equivalent. [65][66][67] In rodent models of PD, dopamine neuron loss is accompanied by increased expression of Ang II AT1 receptor and nicotinamide adenine dinucleotide phosphate (NAPDH) oxidase complex, [25][26][27][28]68 which is a primary source of reactive oxygen species (ROS), and enhanced ROS generation plays a critical role in cell death and pathogenesis. However, ROS derived from NADPH oxidase contribute to self-renewal 69 and lineage determination in NSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Whether AHN is affected in AD brain and, even more fundamentally, whether AHN occurs in adult and aging human brain at all, has been a returning issue of controversy (Boldrini et al, 2018; Eriksson et al, 1998; Gatt et al, 2019; Kempermann et al, 2018; Knoth et al, 2010; Lucassen et al, 2019, 2020; Paredes et al, 2018; Snyder, 2019; Sorrells et al, 2018; Spalding et al, 2013; Tartt et al, 2018). The discussion has taught the paramount importance of accurate interpretation of histological findings, sample stratification (to minimize confounding factors such as agonal state, coexisting brain pathology, neuroinflammation, medication), postmortem delay, tissue preservation, marker labeling methodology, and inclusion of stereology during data analysis (Kempermann et al, 2018; Lucassen et al, 2019, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence has demonstrated that neurogenesis occurs in adult human brain, is impaired in Alzheimer’s Disease (AD) patients and could contribute to the memory decline observed in AD pathology (Boldrini et al, 2018; Cipriani et al, 2018; Gatt et al, 2019; Kempermann et al, 2018; Lucassen et al, 2019, 2020; Moreno-Jiménez et al, 2019; Mu and Gage, 2011; Tartt et al, 2018; Tobin et al, 2019). Boosting adult hippocampal neurogenesis (AHN) was recently proposed as a putative therapeutic approach in AD (Choi and Tanzi, 2019; Choi et al, 2018; Lucassen et al, 2020), yet knowledge about the molecular mechanisms that can be used to leverage AHN is currently missing.…”
Section: Introductionmentioning
confidence: 99%